Psychological and sociological factors influencing police officers' decisions to use force: A systematic literature review. (May 2020) - Cojean, Sébastien; Combalbert, Nicolas; Taillandier-Schmitt, Anne
Abstract: Aim: Police action is frequently discussed and almost always monitored. The aim of this systematic review is to identify the psychological and social factors underlying police officers' decisions to use force. Methodology: Scientific articles were selected from six databases (PsycINFO, PsycARTICLES, Psychology and Behavioral Sciences Collection, HeinOnline, ScienceDirect, PubMed). Results: We found 923 articles matching our search, and 52 were retained based on their results regarding the psychological factors underlying police officers' decisions to use force and the decision-making process itself. We found that the most frequently studied factors were belonging to an ethnic minority, carrying a conducted energy device (CED), the police department's policies and managerial organization, and the environment in which the encounter occurred. However, it seems that the most predictive factor in the decision to use force is the resistance and behavior of the suspect.